Stanimir Panayotov in Conversation with Elisabeth von Samsonow: “We Are Wanted by the Earth”: Станимир Панајотов во разговор со Елизабет вон Самсонов: „Земјата нѐ бара“ - Panayotov, Stanimir; von Samsonow, Elisabeth; Šišovski, Jordan (Identities: Journal for Politics, Gender and Culture, 2016)
Author(s): Stanimir Panayotov and Elisabeth von Samsonow | Станимир Панајотов и Елизабет вон Самсонов Title (English): Stanimir Panayotov in Conversation with Elisabeth von Samsonow: “We Are Wanted by the Earth” Title (Macedonian): Станимир Панајотов во разговор со Елизабет вон Самсонов: „Земјата нѐ бара“ Translated by (English to Macedonian): Jordan Šišovski | Јордан Шишовски Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 12, No. 1-2 (Winter 2015 - Summer 2016) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 81-101 Page Count: 20 Citation (English): Stanimir Panayotov and Elisabeth von Samsonow, “Stanimir Panayotov in Conversation with Elisabeth von Samsonow: ‘We Are Wanted by the Earth,’” Identities: Journal for Politics, Gender and Culture, Vol. 12, No. 1-2 (Winter 2015 - Summer 2016): 81-100. Citation (Macedonian): Станимир Панајотов и Елизабет вон Самсонов, „Станимир Панајотов во разговор со Елизабет вон Самсонов: ,Земјата нѐ бара‘“, превод од англиски Јордан Шишовски, Идентитети: списание за политика, род и култура, т. 12, бр. 1-2 (зима 2015 - лето 2016): 81-101.